A Handbook on “Classification of Drugs” - Saxena, Anil Kumar (2011)
There are plenty text books on the subject of Pharmacology & Therapeutics, but unfortunately we do not have a single book where the drugs are classified in each topic/chapter of Pharmacology. It can be appreciated how difficult it is to remember and memorize the names of drugs especially when the subject of Pharmacology has expended enormously. This handbook on Classification of Drugs lists the commonly used drugs belonging to each chapter in the subject of Pharmacology. This encompasses the drugs used for the treatment and management of various conditions/diseases at one place. Therefore, without opening the heavy and lengthy text books of Pharmacology, a learner can very nicely and affectively use this handbook for knowing the various important drugs used for any medical condition/disease. Since the booklet is very handy and students can keep it in their pocket and can go through the names of drugs quite often. This should help them in memorizing the names of large number of drugs in an easier way. Once this booklet is out in the market it will indeed be very useful to Medical, Dental, Pharmacy students as well as to Clinicians, Nurses and Health Care workers.